2019
DOI: 10.1016/j.automatica.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Co-design of safe and efficient networked control systems in factory automation with state-dependent wireless fading channels

Abstract: In factory automation, heterogeneous manufacturing processes need to be coordinated over wireless networks to achieve safety and efficiency. These wireless networks, however, are inherently unreliable due to shadow fading induced by the physical motion of the machinery. To assure both safety and efficiency, this paper proposes a state-dependent channel model that captures the interaction between the physical and communication systems. By adopting this channel model, sufficient conditions on the maximum allowab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The codesign problem in NCS is often reduced to a joint stabilization and optimization formulation under the constraints of limited channel capacity and control resource. This joint stabilization/optimization problem can be classified into several categories according to communication resource/channel characteristics (eg, transmission power, [11][12][13][14] data rate, 15,16 bandwidth, 17,18 or network topology 19 ) and imperfections (eg, delay and packet dropout 11,12,16 ). In terms of guaranteeing the energy efficiency in NCS, prior work 12 has shown that optimal codesign of both transmission power and control policies for linear dynamical system over wireless fading channel can be decoupled by placing restrict assumptions on the information structure.…”
Section: Relevant Work and Contributionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The codesign problem in NCS is often reduced to a joint stabilization and optimization formulation under the constraints of limited channel capacity and control resource. This joint stabilization/optimization problem can be classified into several categories according to communication resource/channel characteristics (eg, transmission power, [11][12][13][14] data rate, 15,16 bandwidth, 17,18 or network topology 19 ) and imperfections (eg, delay and packet dropout 11,12,16 ). In terms of guaranteeing the energy efficiency in NCS, prior work 12 has shown that optimal codesign of both transmission power and control policies for linear dynamical system over wireless fading channel can be decoupled by placing restrict assumptions on the information structure.…”
Section: Relevant Work and Contributionsmentioning
confidence: 99%
“…Under newly defined mild assumptions, the derived conditions are convex (ie, have linear or quadratic structures) and are thus different from nonconvex condition that were developed in prior works. 11 As a result, the newly proposed conditions can be examined computationally in a more efficient manner. • The second contribution of this paper is the formulation of more computationally efficient methods for solving the codesign problem of NCS.…”
Section: Relevant Work and Contributionsmentioning
confidence: 99%
See 3 more Smart Citations